Special Technical Ability of Pontianak Takraw Athletes - Destriana, Destriana01; Richad Victorian, Ahmad (UNIB Press, 2023)
This study aims to provide a real description of the special skills of Pontianak athletes' sepaktakraw, namely service and smash skills which are special techniques that are very important in the game of sepaktakraw where this technique can make a maximum contribution to the acquisition of points when competing. The description of the results of this special skill can be used as input for athletes, coaches, coaches to always pay attention in the coaching and training process. The sepak takraw game itself is a game that has been competed at the regional, national, regional and international levels. PSTI is the parent organization of sepaktakraw, sepaktakraw achievements, especially in Pontianak, still need intensive coaching, athletes' achievements that have not been maximized at the national level need special attention for coaches, coaches, and athletes. Mastery of basic engineering skills and special techniques needs intensive attention. The preparation of an exercise program requires accurate data to be able to provide the right treatment in the training process. It is important that there is preliminary data related to the level of special skills mastered by Athlete sepak takraw Pontianak. This study presents service and smash skills data with a total of 30 research athletes conducted in Pontianak. From the measurement test results for service Athletes who got the very high category were 3 (22.5%), high category 6 (20%), medium category 11 (37%), low category 8 (27%), and very low category 2 (7%). Smashes of very high category totaled 3 (10%), high category 9 (30%), medium category 13 (43%), low category 5 (17%), and very low category 0 (0%).